Stone Clearance and Duration of Surgery in Percutaneous Nephrolithotomy Using Laser versus Pneumatic Lithotripsy: Laser versus Pneumatic Lithotripsy in Kidney Stone Surgery - Kathia, Usama Muhammad; Ali, Azfar; Ahmad, Mohammad; Khan, Umair Hayat; Khan, Qaisar Abbas; Alvi, Ammar Tariq; Akbar, Muhammad Faizan; Gondal, Khizar Hayat (Pakistan Journal of Health Sciences, 2025)
Nephrolithiasis is common ailment causing pain and renal impairment. Management strategies depend on stone size and location, with stones larger than 2 cm treated with Percutaneous Nephrolithotomy (PCNL). This study compares two energy sources pneumatic lithoclast and Holmium: YAG laser used in PCNL, focusing on stone-free rate and surgery duration. Objective: To know of any difference in Ho:YAG laser and pneumatic probe in terms of stone free rate and surgery duration during PCNL. Methods: This study was conducted retrospectively at the Department of Urology, Lahore General Hospital. The data of patients admitted from June 13, 2021, to June 12th, 2022, was taken. 120 patients were enrolled in this study (60 each for pneumatic lithoclast and Ho: YAG laser), using a non-purposive consecutive sampling technique. Data collection included demography, stone size, site, side, clearance status, and surgery duration. Analysis was conducted using SPSS version 21.0, with quantitative variables assessed via t-tests and qualitative variables via chi-square tests. A p-value ≤ 0.05 was considered statistically significant. Results: Mean age was 36.6±12.68 years in the pneumatic group and 40.40±8.29 years in the laser group. Stone clearance rates were 60% (n=36) for the pneumatic group and 70% (n=42) for the laser group. Mean surgery duration was shorter in pneumatic group (44.87±22.85 minutes) compared to laser group (142±29.41 minutes). Conclusion: Pneumatic lithoclast and Holmium: YAG laser provides comparable stone clearance rates for PCNL. However, the pneumatic probe reduces surgery duration.